A "Supportive and Catalytic" Supervisor? UNHCR's Role in the Global Compact for Refugees. (7th December 2020) - Kinchin, Niamh
ABSTRACT: The Global Compact for Refugees describes UNHCR as its 'supportive and catalytic' leader. The ability for UNHCR to negotiate and collaborate within a highly political environment is critical to the Refugee Compact's ongoing success. However, the Refugee Compact is non-binding, which means that there is no call for UNHCR to exercise its supervisory mandate. By removing the impetus for enforcement, which includes submissions to courts and parliaments, and State admonishment, the Refugee Compact diminishes the non-political elements of UNHCR's work. The consequence of sidelining UNHCR's supervisory mandate is that State interests are elevated above those of refugees, which risks diluting principles of international law and human rights. Entrenched problems of voluntary funding are ignored, and whilst robust conversations may flourish within this forum, realizable outcomes will be undermined by 'endless conversations' and positive optics. UNHCR's moral authority, which stems from its embodiment of the protector of refugees, will not act as a motivation for State action. A reconsideration of UNHCR's role is required in order to allow UNHCR to refocus on its supervisory mandate and to ensure the Refugee Compact can strike a balance between being "entirely non‐political in nature" and the reality of international cooperation, which is inherently political.